THE BIRCH CREEK CANIDS AND DOGS AS TRANSPORT LABOR IN THE INTERMOUNTAIN WEST. Issue 1 (1st February 2019) - Welker, Martin H.; Byers, David A.
Abstract : Historically, domestic dogs (Canis familiaris) have been documented as central features of Intermountain West and Great Plains Native American camps. Some of these dogs were bred specifically for largeness and stamina to haul travois and to carry pannier-style packs. Ethnographic accounts frequently highlight the importance of dogs in moving through the Intermountain West and the plains, reporting loads as heavy as 45 kg (100 lbs). We calculated body mass from skeletal morphometric data and used these to estimate prehistoric and historic dog load capacities for travois and pannier-style packs in the Intermountain West, Great Plains, and Great Basin. Specimens of large dogs recovered from sites in the Birch Creek Valley in Idaho and on the Great Plains indicate the animals could carry weights comparable to ethnographically recorded loads. Further, direct dating of the Birch Creek dog specimens indicated that dogs of this size have been present in the Intermountain West for more than 3, 000 years. These data have important implications for our understanding of prehistoric mobility in the Intermountain West and the plains and suggest that the use of dogs in transporting cargo may have begun as early as 5, 000 years ago. Abstract : El perro doméstico (Canis familiaris) fue una presencia fundamental en los campamentos del Oeste Intermontano y las Grandes Llanuras. Algunos perros fueron criados específicamente para tener gran tamaño y aguante y fueron utilizados para transportar travois (camillas) y cargar alforjas. Los informes etnográficos a menudo resaltan la importancia de los perros para la movilidad en el Oeste Intermontano y las Grandes Llanuras y reportan cargas de hasta 45 kg (100 lbs). En este artículo calculamos la masa corporal a partir de los datos morfométricos del esqueleto y la utilizamos para estimar la capacidad de carga con travois y alforjas de perros prehistóricos e históricos en el Oeste Intermontano, las Grandes Llanuras y la Gran Cuenca. Estos datos indican que los perros de gran tamaño recuperados en contextos arqueológicos del Valle de Birch Creek en Idaho y de sitios de las Grandes Llanuras fueron capaces de transportar cargas con rangos de peso comparables a los reportados etnográficamente. Además, la datación directa de los perros de Birch Creek indica que perros de este tamaño estuvieron presentes en el Oeste Intermontano por más de 3.000 años. Estos datos tienen implicaciones importantes para entender la movilidad prehistórica en el Oeste Intermontano y las Grandes Llanuras, y sugieren que el uso de perros para el transporte de carga podría haber comenzado hace tanto como 5.000 años.